ChemInform Abstract: Crystal Growth, Structural Characterization, and Magnetic Properties of New Uranium(IV) Containing Mixed Metal Oxalates: Na2U2M(C2O4)6 (H2O)4 (M: Mn2+, Fe2+, Co2+, and Zn2+). Issue 20 (25th April 2013) - Yeon, Jeongho; Smith, Mark D.; Sefat, Athena S.; zur Loye, Hans‐Conrad
Abstract The new title oxalates are synthesized via a hydrothermal route employing U(C2O4)2(H2O)6 as the UIV precursor and the respective metal chlorides MCl2 (autoclave, 150 °C, 2 d).